Blocking neutrophil diapedesis prevents hemorrhage during thrombocytopenia - Hillgruber, Carina (J Exp Med, 2015)
Spontaneous organ hemorrhage is the major complication in thrombocytopenia with a potential fatal outcome. However, the exact mechanisms regulating vascular integrity are still unknown. Here, we demonstrate that neutrophils recruited to inflammatory sites are the cellular culprits inducing thrombocytopenic tissue hemorrhage. Exposure of thrombocytopenic mice to UVB light provokes cutaneous petechial bleeding. This phenomenon is also observed in immune-thrombocytopenic patients when tested for UVB tolerance. Mechanistically, we show, analyzing several inflammatory models, that it is neutrophil diapedesis through the endothelial barrier that is responsible for the bleeding defect. First, bleeding is triggered by neutrophil-mediated mechanisms, which act downstream of capturing, adhesion, and crawling on the blood vessel wall and require Gα(i) signaling in neutrophils. Second, mutating Y731 in the cytoplasmic tail of VE-cadherin, known to selectively affect leukocyte diapedesis, but not the induction of vascular permeability, attenuates bleeding. Third, and in line with this, simply destabilizing endothelial junctions by histamine did not trigger bleeding. We conclude that specifically targeting neutrophil diapedesis through the endothelial barrier may represent a new therapeutic avenue to prevent fatal bleeding in immune-thrombocytopenic patients.